Rapid Visual Screening for Seismic Assessment of Hospital Buildings: A Case Study of Kabul City - Abdul Ali Raoufy; Ali Kheyroddin; Hosein Naderpour (Journal of Rehabilitation in Civil Engineering)
Considering the unexpected occurance of natural and man-made disasters over the world including Afghanistan, the importance of hospitals preparedness, as the first reference points for people to get healthcare services, becomes clear. Hospitals as critical infrastructures play an essential role in reducing casualties after an earthquake. The present research was conducted to evaluate the seismic vulnerability of the existing hospital buildings in Kabul City, with the aim of evaluating the current state of hospitals in terms of structural resistance. In the current applied research, the seismic vulnerability of 26 hospitals that had 79 existing buildings were assessed with the Rapid Visual Screening (RVS) technique of FEMA P-154 method in two levels for the first time, and their location was determined by Geographic Information System (GIS). The existing hospital buildings evaluated at level 1 and level 2 were estimated to be seismically vulnerable in the event of a possible destructive earthquake; the seismic vulnerability of these buildings was obtained to be different. Based on the obtained Final Scores, the probability of collapse for these hospitals at level 1 ranged from 3.16% to 59.2%, and at level 2 it ranged from 3.16% to 64%. Based on the results, in the event of destructive phenomena such as earthquakes, there is a probability of damage that would prevent hospitals to provide uninterrupted Immediate Occupancy services. So; these buildings should be prioritized, and subjected to a detailed seismic vulnerability assessment, then solutions to rehabilitation or retrofitting of buildings against earthquakes should be investigated.